Leaf Nutrient Status Vis-à-vis Fruit Yield and Quality of Sweet Orange (Citrus sinensis (L.) Osbeck) - Sudhakar, P.; Reddy, B. Ravindra; Reddy, P. Venkataram Muni; Munaswamy, V.; Reddy, A. Ramanjaneya (Sciencedomain International, 2020)
The present study was conducted to know the effect of leaf nutrient status on fruit yield and quality of sweet orange (Citrus sinensis (L.) Osbeck) in YSR district of Andhra Pradesh, India. In this investigation fifty sweet orange orchards aged between 12 to 13 years were selected and plant samples such as index leaves and matured fruits were collected from 10 per cent of plants in each orchard. Leaf Zn deficiency (62%) was the most severe among the 10 mineral elements tested and followed by Fe (54%), Mn (52%) and Cu (26%). Fruit yield showed significant positive correlation with leaf N (r =0.519**) and P (r =0.409**). Fruit weight had significant positive correlation with leaf Nitrogen (r = 0.469**), Phosphorus (r = 0.446**) and Potassium (r = 0.415**). Fruit juice percent was significantly and positively correlated with leaf N (r =0.353**) and P (r =0.364**). Titrable acidity had significant negative correlation with leaf Fe (r = -0.371**) and leaf Mn (r = -0.292*). Total Soluble Solids (TSS) showed a significant positive relation with leaf P (r = 0.438**) and significant negative correlation with leaf Mn (r = -0.311*). Vitamin C content of the sweet orange fruit had significant positive correlation with leaf N (r = 0.437**), P (r = 0.516**) and K (r = 0.398**).
Keywords: 2. Zero hunger; 15. Life on land